Sensors and Microsystems AISEM 2011 Proceedings - D’Amico, Arnaldo.; D’Amico, Arnaldo.; Di Natale, Corrado.; Di Natale, Corrado.; Mosiello, Lucia.; Mosiello, Lucia.; Zappa, Giovanna.; Zappa, Giovanna. (Lecture Notes in Electrical Engineering,, 2012)
This book contains a selection of papers presented at the 16th AISEM (“Associazione Italiana Sensori e Microsistemi”) National Conference on Sensors and Microsystems, held in Rome 7-9 February 2011. The conference highlighted updated results from both theoretical and applied research in the field of sensors and microsystems. This book presents material in an interdisciplinary approach, covering many aspects of the disciplines related to sensors and microsystems, including physics, chemistry, materials science, biology and applications. Provides a selection of the best papers from the most recent AISEM conference; Covers a broad range of topics relating to sensors and microsystems, including physics, chemistry, materials science, biology and applications; Offers interdisciplinary coverage, aimed at defining a common ground for sensors beyond the specific differences among the different particular implementation of sensors.              .